Micro-CT for analysis of laser sintered micro-composites. Issue 4 (2nd January 2020) - Wingham, James Robert; Turner, Robert; Shepherd, Joanna; Majewski, Candice
Abstract : Purpose: X-Ray-computed micro-tomography (micro-CT) is relatively well established in additive manufacturing as a method to determine the porosity and geometry of printed parts and, in some cases, the presence of inclusions or contamination. This paper aims to demonstrate that micro-CT can also be used to quantitatively analyse the homogeneity of micro-composite parts, in this case created using laser sintering (LS). Design/methodology/approach: LS specimens were manufactured in polyamide 12 with and without incorporation of a silver phosphate glass additive in different sizes. The specimens were scanned using micro-CT to characterise both their porosity and the homogeneity of dispersion of the additive throughout the volume. Findings: This work showed that it was possible to use micro-CT to determine information related to both porosity and additive dispersion from the same scan. Analysis of the pores revealed the overall porosity of the printed parts, with linear elastic fracture mechanics used to identify any pores likely to lead to premature failure of the parts. Analysis of the additive was found to be possible above a certain size of particle, with the size distribution used to identify any agglomeration of the silver phosphate glass. The particle positions were also used to determine the complete spatial randomness of the additive as a quantitative measure of the dispersion. Practical implications: This shows that micro-CT is an effective method of identifying both porosity and additive agglomeration within printed parts, meaning it can be used for quality control of micro-composites and to validate the homogeneity of the polymer/additive mixture prior to printing. Originality/value: This is believed to be the first instance of micro-CT being used to identify and analyse the distribution of an additive within a laser sintered part.